Demersal fish resources in Malaysian waters: 3rd east coast trawl survey off the East Coast of Peninsular Malaysia (14th August - 20th September 1972) - Lam, Wah Chang (Kuala Lumpur : Kementerian Pertanian dan Pembangunan Luar Bandar), 1975)
28